Does changing the plane of abduction influence shoulder muscle recruitment patterns in healthy individuals?. (February 2016) - Reed, Darren; Cathers, Ian; Halaki, Mark; Ginn, Karen A.
Abstract: Study design: Observational laboratory study. Background: Abduction is a movement commonly used in the assessment of shoulder dysfunction and prescription of exercises to improve shoulder function. Abduction in the scapular and coronal planes are used interchangeably. It is not known if the activation of individual shoulder muscles differ between abduction performed in these planes and therefore, if they represent different tests/exercises. Objective: To quantify and compare the muscle activation patterns and levels for each shoulder muscle during abduction performed in the scapular plane with that performed in the coronal (scapular −30°) and scapular +30° planes. Methods: Electromyographic recordings were taken from eight shoulder muscles of fourteen healthy volunteers during shoulder abduction in the scapular and coronal planes and in a plane 30° anterior to the scapular plane (scapular +30°) at 50% of maximum load. Results: Similar average muscle activation levels were demonstrated during abduction in the scapular plane and within a 30° arc of this plane for all muscles except: middle deltoid (5% MVC higher activation in the coronal and 4% MVC lower activation in the scapular +30° plane) and upper trapezius (6% MVC lower activation in the scapular +30° plane). Activation patterns between planes for all muscles were similar (ICC(3, 1)  ≥ 0.87). Conclusions: Abduction can be performed within a 30° arc of the scapular plane with no change in shoulder muscle activation patterns. Only middle deltoid activation levels change between the scapular and coronal planes and middle deltoid and upper trapezius between the scapular and scapular +30° planes. Highlights: Shoulder muscle activity is investigated during abduction performed in three planes. Scapular plane abduction is used as the reference plane. Individual shoulder muscle activation patterns are similar in all three planes. Only deltoid and upper trapezius activity levels show small variation between planes. Scapular plane abduction is a similar exercise to abduction performed in other planes.